Fear in the Mirror: the Earthquake in Chile in Juan Villoro’s Novel - Aloe, Francesco (Governare la paura. Journal of interdisciplinary studies, 2013)
The 27th February, 2010 an 8.8 Mw earthquake upset Chile. A year after, the writer Juan Villoro published 8.8: El miedo en el espejo, a story by means of a catharsis telling his own experience throughout the earthquake. Villoro’s aim is to demonstrate that people’s psychological guaranties have fallen down together with the buildings’ walls. The Mexican writer describes his staying at the Hotel San Francisco in Santiago de Chile, which held out against the earthquake shocks but entrapped several Latin-American writers as well as Villoro. All the writers were guests at the Congreso Iberoamericano de Literatura Infantil y Juvenil. Villoro book’s purpose is to reflect upon how fear impacts the human beings.